2014
DOI: 10.1645/13-190.1
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of an ELISA Test for Diagnosing Oestrosis in Iberian Ibex

Abstract: Oestrosis is one of the most prevalent parasitosis affecting the Iberian ibex, Capra pyrenaica . To date, both the diagnosis of oestrosis and the determination of the intensity of parasitism require the use of invasive methods (necropsy), which necessarily limit research possibilities. We analyzed the immune humoral response (IgM and IgG) against Oestrus ovis L. excretory/secretory larval antigens in 32 sera taken from Iberian ibex from the Sierra Nevada Natural Space (southern Spain). Three antigens were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…While IgG-anti O. ovis means remained low in treated groups, the control lambs showed an increase in averages at the end of the trial, thus indicating that the animals were responding to parasite infestation. Previous studies demonstrated that detection of O. ovis antibodies in sheep is a valid diagnosis technique ( 24 , 37 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…While IgG-anti O. ovis means remained low in treated groups, the control lambs showed an increase in averages at the end of the trial, thus indicating that the animals were responding to parasite infestation. Previous studies demonstrated that detection of O. ovis antibodies in sheep is a valid diagnosis technique ( 24 , 37 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the lambs became infested with O. ovis at an early age and the larval burden was not associated with specific IgG levels. Since oestrosis is a common problem in sheep, a serological diagnosis may be useful for identifying animals that are carrying O. ovis and for avoiding underestimation of the number of parasitized animals, as often happens when using purely visual diagnostic methods (ARIAS et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The results from previous studies demonstrated that the ELISA test (enzyme-linked immunosorbent assay) is a valid technique for detecting O. ovis antibodies in sheep (ALCAIDE et al, 2005;ANGULO-VALADEZ et al, 2008;SILVA et al, 2012b;ARIAS et al, 2014) and might be useful as an alternative to postmortem examination. Therefore, the present study was carried out to evaluate the immune humoral response among lambs, from birth to slaughter, in terms of anti-O.…”
Section: Introductionmentioning
confidence: 99%
“…Other important factors that are difficult to model because they are not fully understood are related to parasite embryonic development, its reproductive success (generally below its biotic potential; Colwell 2001), the behaviour of adult flies during reproduction, host seeking and larviposition related to the defensive behaviour of hosts (Anderson 2006a), the immune response of hosts (Arias et al 2014), the influence of the programmes for treating and controlling oestrosis (Colwell et al 2009), and even the number of hosts present in a given area. All of these factors will determine in each case the parasite carrying capacity and the density or abundance of adult flies in a given area.…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring populations of these parasites when working on infected wild hosts is a difficult, timeconsuming task. Several non-invasive methods are available for diagnosing oestrosis in wild hosts, such as Enzyme-Linked Immunosorbent Assay (ELISA) (Arias et al 2014), pharyngeal endoscopy (Oksanen et al 1992) or computed tomography (Fidalgo et al 2015). Nevertheless, for epidemiological studies and a proper identification of the parasite species involved, larvae are usually obtained after necropsy (invasive method).…”
Section: Introductionmentioning
confidence: 99%